2019
DOI: 10.1073/pnas.1818585116
|View full text |Cite
|
Sign up to set email alerts
|

An unbiased approach elucidates variation in ( S )-(+)-linalool, a context-specific mediator of a tri-trophic interaction in wild tobacco

Abstract: Plant volatile organic compounds (VOCs) mediate many interactions, and the function of common VOCs is especially likely to depend on ecological context. We used a genetic mapping population of wild tobacco, Nicotiana attenuata, originating from a cross of 2 natural accessions from Arizona and Utah, separated by the Grand Canyon, to dissect genetic variation controlling VOCs. Herbivory-induced leaf terpenoid emissions varied substantially, while green leaf volatile emissions were similar. In a field experiment,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
57
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 49 publications
(65 citation statements)
references
References 64 publications
7
57
1
Order By: Relevance
“…To examine this, we further measured the floral volatiles of the 25 genotypes and compared the emissions of ( E )-β-ocimene, linalool and ( E )-α-bergamotene emission in the HIPVs and floral volatiles. We found that linalool, which was found in both floral volatiles and HIPVs, showed no correlation among the different genotypes, consistent with a recent study (He et al ., 2019). However, the variations of ( E )-α-bergamotene and ( E )-β-ocimene emission in HIPVs and floral volatiles were significantly correlated (Figure 1; ( E )-β-ocimene: R 2 = 0.23, P = 0.021; ( E )-α-bergamotene: R 2 = 0.50, P < 0.001).…”
Section: Resultssupporting
confidence: 92%
“…To examine this, we further measured the floral volatiles of the 25 genotypes and compared the emissions of ( E )-β-ocimene, linalool and ( E )-α-bergamotene emission in the HIPVs and floral volatiles. We found that linalool, which was found in both floral volatiles and HIPVs, showed no correlation among the different genotypes, consistent with a recent study (He et al ., 2019). However, the variations of ( E )-α-bergamotene and ( E )-β-ocimene emission in HIPVs and floral volatiles were significantly correlated (Figure 1; ( E )-β-ocimene: R 2 = 0.23, P = 0.021; ( E )-α-bergamotene: R 2 = 0.50, P < 0.001).…”
Section: Resultssupporting
confidence: 92%
“…Interestingly, in this case, S. frugiperda moths were attracted by conspecificinduced plant volatiles, especially DMNT, which highlights the fact that HIPVs play different roles in different plant-insect interactions, i.e. the effect of plant volatiles is contextdependent (He et al 2019).…”
Section: Discussionmentioning
confidence: 77%
“…Three additional suites of transgenic lines in which the key components of the SL and KAR signaling pathways, including D14, CCD7, and KAI2 genes (S2A and S2B Fig), were silenced by RNAi were generated (Fig 1A and 1C). For each silencing construct, we selected two independent transgenic lines, which harbored a single complete insertion of the inverted repeat RNAi construct, as verified by several NanoString probes (S2C-S2E Fig) [42]. A transgenic line transformed with an empty vector (EV) was used as control plants [11].…”
Section: Max2 D14 and Ccd7 Plants But Not Kai2 Plants Produce Mormentioning
confidence: 99%
“…T 2 plants were used in all experiments. The number of insertion copies as well as the fidelity of the insertion (over-reads and truncations) were evaluated by NanoString [42]. In brief, DNA extracted from individual transgenic plants was used for NanoString to detect the content of inserted fragments according to the designed probes.…”
Section: Plant Materials and Growing Conditionsmentioning
confidence: 99%
See 1 more Smart Citation